PENGARUH ZAKAT DIGITAL TERHADAP PENGENTASAN KEMISKINAN DI ERA DIGITAL - Farid, Diana; Abdulah Pakarti, Muhammad Husni; Fathiah, Iffah; Hendriana, Hendriana (LPPM STAI Muhammadiyah Probolinggo, 2023)
This study aims to investigate the effect of digital zakat on poverty alleviation in the digital era. In the context of growing digitalization, digital zakat becomes an attractive alternative in the collection and distribution of zakat to help those in need. The research method involves searching and analyzing published literature, including scholarly articles, research reports, and books related to digital zakat and poverty alleviation. The data collected will be analyzed qualitatively by identifying key themes that emerge in the relevant literature. These themes will be used to compile research findings that will provide in-depth insights into the influence of digital zakat in alleviating poverty in the digital era. The results of this study show that digital zakat has significant potential in alleviating poverty in the digital era. One of the main advantages of digital zakat is the ease of access and transparency in the collection and distribution of zakat. Through digital platforms, individuals can easily collect and transfer their zakat directly to needy recipients. This reduces the cost and time involved in the traditional process of zakat collection and distribution. In addition, digital zakat also enables a more inclusive approach in alleviating poverty, with more individuals able to participate in giving zakat. This research contributes to the understanding of the effect of digital zakat on poverty alleviation in the digital era. The findings and recommendations from this research can serve as a guideline for zakat institutions, government, and other related organizations in designing and implementing effective digital zakat. It is hoped that this research can encourage further development and wider application of digital zakat for poverty alleviation in the future.